2015
DOI: 10.1159/000369216
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic versus Fluoroscopic Access for Percutaneous Nephrolithotomy: A Meta-Analysis

Abstract: Objective: To assess the safety and efficacy of ultrasonographic vs. fluoroscopic access for percutaneous nephrolithotomy (PCNL). Methods: Medline (PubMed), Embase, Ovid, Cochrane, and the Chinese Biomedical Literature databases were searched to identify clinically controlled trials (CCTs) and randomized controlled trials (RCTs) that compared ultrasonographic access with fluoroscopic access for PCNL. RevMan 5.1 software and Stat Manager V4.1 software were used for the meta-analysis. Results: Five RCTs and nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 23 publications
0
25
1
2
Order By: Relevance
“…RIRS is a safe and effective approach for renal stone treatment in obese individuals, except that RIRS requires long operation time depending on the size, number, and location of stones and on the experience of the surgeon [9] . PCNL is the gold standard first-line treatment for renal stones larger than 2 cm; the use of ultrasonographic access is recommended for PCNL [10] . PCNL is a particularly important therapeutic modality for obese individuals.…”
mentioning
confidence: 99%
“…RIRS is a safe and effective approach for renal stone treatment in obese individuals, except that RIRS requires long operation time depending on the size, number, and location of stones and on the experience of the surgeon [9] . PCNL is the gold standard first-line treatment for renal stones larger than 2 cm; the use of ultrasonographic access is recommended for PCNL [10] . PCNL is a particularly important therapeutic modality for obese individuals.…”
mentioning
confidence: 99%
“…To avoid multiple admissions, surgical procedures, related psychiatric stress and economic cost, some urologists prefer to manage some patients with multiple accesses specially that it has been demonstrated that blood loss and complication rates of the two approaches are comparable [18]. Although Akman and colleagues indicated significant bleeding in multiple-access PCNL, they showed that multi-access PCNL is a highly successful alternative to the single-access approach [17,19,20,21]; nonetheless, none of them have left the patient totally tubeless after multiple accesses.…”
Section: Discussionmentioning
confidence: 99%
“…A 5 F ureteral catheter was then inserted retrogradely into the renal pelvis through cystoscopy or flexible ureteroscopy (URS), and continuous infusion of saline was performed to produce artificial hydronephrosis. The patient was then changed to the prone position [5,6,8]. …”
Section: Methodsmentioning
confidence: 99%
“…Ultrasound-guided percutaneous punctures were made with an 18-gauge coaxial needle into the targeted calix (middle/lower kidney calices) [5,6,8]. The puncture point was in the 12th rib infracostal margin, between the posterior axillary line and scapula line [9].…”
Section: Methodsmentioning
confidence: 99%